a LAYANAN INFORMASI TERHADAP PEMAHAMAN KEKERASAN SEKSUAL BAGI PESERTA DIDIK: a - Mimit Pakasi; Sudirman; M. Fahri Hamdika Putra (IAI DDI POLEWALI MANDAR, 2023)
. The research method uses a quantitative approach with a questionnaire given to students at MTs As'Adiyah Al-Muhajirin. The problems studied in this study are What is the impact of information services on sexual violence in increasing students' understanding at MTs As'Adiyah Al-Muhajirin. The results of the data analysis show that information services provided in a structured and directed manner have a significant positive effect on increasing students' understanding of various aspects of sexual violence. Based on the average scores before and after receiving information services, there was a significant increase in knowledge about the definition of sexual violence, its types, risk factors, and how to report it